Laryngeal tumor volume as a predictor for thyroid cartilage penetration1. Issue 3 (8th April 2012) - Kats, Svetlana S.; Muller, Susan; Aiken, Ashley; Hudgins, Patricia A.; Wadsworth, J. Trad; Shin, Dong M.; Khuri, Fadlo; Beitler, Jonathan J.
Abstract Background Review of laryngectomy specimens demonstrated that preoperative CT scanning is suboptimal in predicting both thyroid cartilage penetration and extralaryngeal spread. We investigated the association between the CT‐based gross tumor volume (GTV) with pathologic evidence of thyroid cartilage penetration among patients undergoing laryngectomy for squamous cell carcinoma (SCC) of the larynx. Methods Ninety‐four patients were identified who underwent total laryngectomy for SCC of the larynx. GTV, as defined by preoperative diagnostic CT scan, was contoured and analyzed using treatment‐planning software. Results Among the 49 nonirradiated patients, the mean GTVs of patients with (n = 15) and without (n = 34) thyroid cartilage penetration was 60.1 and 28.0 cm3 (p = .004). When the nonirradiated patients were divided into 3 GTV groups (≤25 cm3, 25–50 cm3, >50 cm3), the rates of thyroid cartilage penetration were 23%, 17%, and 78%, respectively (p = .003). Conclusions Laryngeal tumor volume is associated with pathologic evidence of thyroid cartilage penetration in nonirradiated patients. © 2012 Wiley Periodicals, Inc. Head Neck, 2013